2019
DOI: 10.1001/jamanetworkopen.2019.12895
|View full text |Cite|
|
Sign up to set email alerts
|

Accelerometer- and Pedometer-Based Physical Activity Interventions Among Adults With Cardiometabolic Conditions

Abstract: Key PointsQuestionIs the use of accelerometers and/or pedometers associated with increased physical activity in people with cardiometabolic conditions?FindingsThis systematic review and meta-analysis of 32 randomized clinical trials (4856 participants) found that accelerometer- and pedometer-based interventions were associated with small to medium short-term improvements in physical activity and that consultations with health professionals and pedometers were associated with improved physical activity.MeaningA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 62 publications
(93 reference statements)
3
53
0
Order By: Relevance
“…Some studies provided only graphical presentation of step-count results, which prevented their inclusion in meta-analyses. We were also unable to analyse the importance of both number and length of intervention sessions, due to reporting inconsistencies, which others have also highlighted [96]. Moving forward, therefore, when interventions are being investigated, it is important for study reports to provide clear information about the exact nature of the intervention, the number and length of contacts included within it and the reporting of outcomes, to provide further robust evidence to inform policy.…”
Section: Implications For Public Health Research Practice and Policymentioning
confidence: 99%
“…Some studies provided only graphical presentation of step-count results, which prevented their inclusion in meta-analyses. We were also unable to analyse the importance of both number and length of intervention sessions, due to reporting inconsistencies, which others have also highlighted [96]. Moving forward, therefore, when interventions are being investigated, it is important for study reports to provide clear information about the exact nature of the intervention, the number and length of contacts included within it and the reporting of outcomes, to provide further robust evidence to inform policy.…”
Section: Implications For Public Health Research Practice and Policymentioning
confidence: 99%
“…Application of accelerometers and pedometers was analysed in different cardiometabolic conditions (e.g., diabetes and cardiac disease) in a systematic review [26], which reported increased moderate to vigorous physical activity (MVPA) levels with either pedometers or accelerometers specifically when face to face consultation with the health professionals was executed. Regular advice and guidance on exercise or physical activity regime to patients were provided with pedometers and accelerometers separately or in combination yielded higher PA levels with a standardized mean difference of 0.30 (accelerometers) and 0.52 (1703 steps using pedometers).…”
Section: Cardiology Research and Practicementioning
confidence: 99%
“…In comparison, in the HEALD trial, the group receiving pedometers without any counseling (similar to our group B) increased daily steps to a lower extent than the group receiving counseling (30). Meta-analyses provide con icting results regarding the e cacy of counseling as a complement to self-monitoring (8,9). The speci c content of the intervention components may in uence both the implementation and the outcomes of an intervention.…”
Section: The Hypothesis Of Sophiamentioning
confidence: 78%
“…Diabetes care givers are encouraged to give advice on physical activity and such advice may be combined with using a pedometer or a comparable self-monitoring device (4, 5). Pedometers have shown positive effects on increased physical activity in short term in populations with type 2 diabetes (3,(6)(7)(8)(9) and are recommended for use to increase motivation to be physically active (10,11). Yet, it is unclear whether self-monitoring alone, or in combination with counseling is the most feasible and effective alternative (8,9,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation